Knitting Indonesian Unity in the Momentum of Mohammad Natsir's Integral Motion: Studi analyses - Mohamad Latif; Muhamad Fajar Pramono; Muqit Nur Rohman; Amir Reza, Amir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Unity is an important aspect of a state institution. Unity can be a strength for a nation and state. One of the historical moments that seeks to unite Indonesia after the proclamation is Natsir's Integral Motion. The concept promoted by Indonesian Muslim political figure Mohammad Natsir succeeded in uniting Indonesia into the Republic of Indonesia from the previous RIS (United Republic of Indonesia). This article will discuss the role of Mohammad Natsir with his integral motion in building unity and integrity in Indonesia. This research is library research and the data source used consists of primary data sources of Mohammad Natsir's works related to the Integral Movement and Indonesian Unity, and is assisted by secondary data sources, namely books, which are relevant to this research to strengthen arguments and to complete the data from the research results. The data analysis technique used by the author in this research is content analysis. The results that the author got from this study are that Natsir's Integral Motion has a big and important influence on Indonesia. Not only does it unite Indonesia, but it also has a significant influence in the fields of politics, economics, education and international relations. Based on these findings, the author hopes that there will be further studies on Natsir's integral motion, so that it can become material for reflection and discussion together.